Editor Thank You to Reviewers for 108(4) - Lauri Baker; Holli Leggette; Annie R. Specht; Anissa Mattox (Journal of Applied Communications, 2025)
The editors of 108(4) would like to thank the reviewers of this issue. We have also included a note on new journal processes.
Keywords: Reviewers; Editors